Amplified fragment length polymorphisms, the evolution of the land snail genus Theba (Stylommatophora: Helicidae), and an objective approach for relating fossils to internal nodes of a phylogenetic tree using geometric morphometrics. (20th March 2014) - Haase, Martin; Greve, Carola; Hutterer, Rainer; Misof, Bernhard
<x xml:space="preserve">Abstract</x> Time‐trees are commonly calibrated based on fossils attributed to internal nodes, thus defining the minimum age of these nodes. However, in the absence of synapomorphies, the phylogenetic position of a fossil can only be inferred based on similarity. In this study, we objectively allocated fossil shells to internal nodes based on the reconstruction of ancestral shapes and sizes in a geometric morphometric framework. Our phylogenetic analysis of 24 (putative sub)species was based on 2524 amplified fragment length polymorphism loci. In this well‐supported tree the taxa occurring in north‐west Africa and on the Iberian peninsula were paraphyletic with respect to the (sub)species from the Canary and Selvagen Islands, indicating a continental origin of the genus in contrast to our earlier sequence‐based account. Ancestral shell shapes and sizes were inferred based on landmark data using squared‐change parsimony. In a subsequent principal component analysis, only three of 20 fossil shells could be unequivocally allocated to internal nodes. However, these fossils were all Quaternary, and thus too young to infer meaningfully narrow confidence intervals for divergence estimates that probably reach back into the Miocene or even Oligocene. The apparent failure of allocating older fossils to internal nodes and achieving a reliable tree calibration was caused by the absence of phylogenetic signal in the shells of Theba due to extensive, sometimes rapid, convergent evolution, including reversals. © 2014 The Linnean Society of London